2023
DOI: 10.1161/circresaha.123.322750
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Filamin C With Actin Is Essential for Cardiac Development and Function

Abstract: Background: FLNC (filamin C), a member of the FLN family predominantly expressed in striated muscles, plays a crucial role in bridging the cytoskeleton and ECM (extracellular matrix) in cardiomyocytes, thereby maintaining heart integrity and function. Although genetic variants within the N-terminal ABD (actin-binding domain) of FLNC have been identified in patients with cardiomyopathy, the precise contribution of the actin-binding capability to FLNC’s function in mammalian hearts remains poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…FLNC is an actin-binding and crosslinking protein with an important role in maintaining the structural integrity of Z-discs, intercalated discs, and cell membranes of cardiomyocytes [30][31][32]. In this study, we showed that the complete loss of FLNC dysregulates the assembly of thin filament bundles and the focal adhesion signaling…”
Section: Discussionmentioning
confidence: 66%
“…FLNC is an actin-binding and crosslinking protein with an important role in maintaining the structural integrity of Z-discs, intercalated discs, and cell membranes of cardiomyocytes [30][31][32]. In this study, we showed that the complete loss of FLNC dysregulates the assembly of thin filament bundles and the focal adhesion signaling…”
Section: Discussionmentioning
confidence: 66%